CORELATION OF PARENTS' PROFILES OF CHILDREN WITH LATE CLEFT REPAIR IN SURABAYA CLEFT LIP AND PALATE CENTRE (JANUARY 2015–DECEMBER 2017) - Ningrum, Laras Puspita; Saputro, Iswinarno Doso; Zarasade, Lobredia (Jurnal Rekonstruksi dan Estetik, 2020)
Highlights: Economic factors and insufficient information about cleft palate treatment was the primary cause of delayed repairs,except for Parents' education levels. The essential responsibility of primary care physicians is to provide education on treatment stages to minimize delays. Abstract: Introduction:  Optimal time of Cleft palate repair is during the 10 to 12 month of  age.  In  this  time  produce  far  natural  results  in  terms  of  speech  because  it enabled  the  maturation  of  scar  tissue  postoperatively.  The  soft  palate  must function  properly before the  patient  starts learning  to  talk,  otherwise  speech disorders such as persistent rhinolalia aperta might arise. In pediatric patients, the role of parents is very important on adherence to therapy. Methods: This is a cross-sectional study. The first study group was parents of patients who had surgical repair before two years old and the second group was the parents  of  patients  who  had  repair  after  two  years  old.  We  compared  age, monthly income, education level, number of children, and residential distance from Surabaya of the two groups. Results:  The  data  of  this  study  were  obtained  from  the  medical  records  of patients with cleft lip surgery at CLP Center Surabaya in 2015th-2017th with total  of  358  patients,  172  were  female  and  186  were  male.  52  patients  with delayed cleft palate surgery. Patients' parents in both groups were mostly 31- 40 years old, were high school graduated, has one child, earned less than 1.5 million rupiah a month, and lived less than 100 kms from Surabaya. From the statistical  results,  parent's  income  has  the  strongest  correlation  with  the patient's age in cleft palate surgery (-2.7). A negative coefficient means that the less parent's income, the more patient likely had delayed cleft palate surgery. While other factors found weak and very weak correlations. Conclusions:The  results  form  patient's  parents'  interview,  concluded  that besides economic factors, the lack of information cleft palate treatment is the key  factors  that contributed to  the  delay  of  cleft  palate  repair.  The education level  does  not  affect  the  delay  in  cleft  palate  surgery,  because  even  in  high educated parents, sometimes they don't understand the stages of cleft lip and palate  treatment.  This  study  emphasized  the  necessity  to  educate  about  the stages of surgery by primary care physicians, to minimize delays.